Acoustic and fluorescence data from: A marine zooplankton community vertically structured by light across diel to interannual timescales - Hobbs, Laura; Banas, Neil; Cohen, Jonathan; Cottier, Finlo; Berge, Jørgen; Varpe, Øystein (Dryad, 2021)
The predation risk of many aquatic taxa is dominated by visually
searching predators, commonly a function of ambient light.
Several studies propose that changes in visual predation will
become a major climate-change impact on polar marine ecosystems.
The high Arctic experiences extreme seasonality in the light
environment, from 24-h light to 24-h darkness, and therefore
provides a natural laboratory for studying light and
predation risk over diel to seasonal timescales. Here, we show
that zooplankton (observed using acoustics) in an Arctic fjord
position themselves vertically in relation to light. A single
isolume (depth-varying line of constant light intensity, the
value of which is set at the lower limit of
photobehaviour reponses of Calanus spp. and krill.) forms a
ceiling on zooplankton distribution. The vertical distribution is
structured by light across timescales, from the deepening of
zooplankton populations at midday as the sun rises in spring, to
the depth to which zooplankton ascend to feed during
diel vertical migration. These results suggest that zooplankton
might already follow a foraging strategy that will keep visual
predation risk roughly constant under changing light conditions,
such as those caused by the reduction of sea ice, but likely with
energetic costs such as lost feeding opportunities due to altered
habitat use.
Data were collected from moorings installed at ~ (78°N 11°E)
(Kongsfjorden, Svalbard). Full details of mooring deployments and
processing can be found in Table S1 of the associated
paper.
All scripts refer to the two .mat files. For greater accessibility, data
are also avaialable through an Excel spreadsheet.